MANAJEMEN BANDWIDTH MENGGUNAKAN DELAY POOLS DI SQUID PROXY (STUDI KASUS : SMA N 1 SRAGEN) - Kurnianto, Catur Andi; Suraya, Suraya; Nurnawati, Erna Kumalasari (Jurnal Jarkom, 2013)
ABSTRACTÂ The computer network is a collection of computers that are connected to each other and work automatically . It can affect the stability of the internet connection that is the amount of bandwidth used and how effective the network bandwidth can be utilized . Bandwidth is a measure of the amount of information that can flow from one place to another within a certain time. Delay pools allows the administrator to limit bandwidth usage can be used by the user and also limit the bandwidth that can be used by a particular file type . One type of method of managing bandwidth using squid . Squid is a caching application GPL ( GNU Public License ) and an implementation of a proxy server that can store objects in the cache . Delay Pools is an innate feature of squid that are used to perform bandwidth management. In this system of testing , including testing includes downloads , uploads , content - filtering and blocking adult content social media during work hours . In testing the download and upload can be seen that the system is able to divide bandwidth fairly to all users . To test the content filtering system using two methods, namely filtering with delay pools and the DNS Nawala . Then the system is also blocking social media access during business hours so that the learning process can proceed smoothly .Â Keywords : computer networks , bandwidth , squid , delay pools , DNS Nawala